The role of the mind in understanding the Qur’an and Sunnah Specialization: Islamic Fiqh and jurisprudence of Fiqh (Journal of the College of Basic Education, 2022)
The relationship between mind and transport is old and present at the same time, inherited by schools of thought through the stages of the development of human thought, the Islamic school was not indispensable. And entered the Islamic thought of the widest door, and has been the subject of deep debate in most schools of thought in Islam, about which has precedence of mind or transport in understanding the Quran and Sunnah, and through the presentation of doctrines of jurisprudence and verbal and philosophical in the identification of concepts of reason and transport, the method used in the use of reason towards revelation is determined by the relationship between them, and denies any conflict, especially in the evidence of legitimacy if is performed against the right mind, but if they break the determinism between them, do not oppose between public transport and the mind of the apparent,but complementarity and interrelationship between them complementary relationship in the knowledge of facts, whether it offers transportation on the mind or vice versa.